'God corresponds to Godself': John Webster's doctrine of God 'after' Karl Barth. Issue 2 (May 2023) - Rempel, Brent
Abstract: The nature and extent of Karl Barth's significance in John Webster's theological formation is widely recognised but remains to be explored in detail. Addressing this lacuna, this essay considers how Barth's doctrine of the triune God animates Webster's teaching on the same. In approaching the topic, I show how Webster carries forward Barth's deep sense of God's aseity in relation to the world and follows Barth in his commitment to the singularity of God's triune being. God's particularity and aseity converge in 'God's self-correspondence' (namely, that God 'in Godself' corresponds to God 'for us'), which represents the core of Barth's influence on Webster's theology proper. The final section responds to Katherine Sonderegger's recent criticism of Webster's 'relationalism', which counts God's relation to creatures as an integral aspect of God's eternal life. I reframe the issue in terms of Webster's late-career retractions of the language of inclusion and divine self-determination, arguing that the difficulties that Sonderegger identifies in earlier writings are overcome in the final decade of Webster's corpus.